UNLOCKING GENERATION Z’S MINDS ON STOCK INVESTMENT: DETERMINANTS OF MOBILE STOCK INVESTMENT APPLICATION ADOPTION - Sembel, Jacquelinda Sandra (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Generation Z is the youngest generation entering the stock markets. Their participation may break or make the future of stock investment. This study aims to investigate the determinants of the adoption of mobile stock investment applications by Generation Z. The study provides new insights into the minds of Generation Z on how their perception of financial risks and benefits, their financial literacy, and financial influencers affect their adoption of mobile stock investments applications in the context of Indonesia. The study used survey questionnaires as research instruments with Partial Least Square-Structural Equation Modeling (PLS-SEM) as the quantitative data analysis tool. This study involved 253 Generation Z who are active students at private universities in Java and Sumatra islands (the two most populous islands in Indonesia). The study found that perceived benefits, perceived technology security, and financial literacy affect the adoption of mobile stock investment applications. Finfluencers and Perceived financial risks were not found to have a positive influence on the adoption of mobile stock investment applications among Generation Z.